ANALISIS MANAJEMEN LOGISTIK PENGELOLAAN OBAT DI PUSKESMAS KOTA KENDARI - Muhammad Sujarwad; Ramadhan Tosepu; Adius Kusnan (NHM PRESS, 2023)
Drug logistics management is a series of activities involving aspects of planning, procurement, storage and distribution of drugs that are managed optimally to ensure the achievement of the accuracy of the quantity, quality and type of drugs. The purpose of this study was to analyze the logistics management of drug management at the Kendari City Health Center. This type of research is a qualitative research using a phenomenological approach, the research location is the Community Health Center in Kendari City. This research was conducted in April 2023 involving subjects from 5 treatment centers in Kendari City. The results of the study show that the formulation of drug requirements plans is carried out periodically, involving collaboration between the pharmaceutical team, the financial sector, and the medical team. Procurement of drug needs is carried out periodically or routinely, either every month, several months, or for a certain period of time, such as 3 months. The process of receiving the drug can be done in the pharmacy department, warehouse room, or a designated place at the Puskesmas. Drug storage that is regulated by taking into account the principles of good drug management. drug collection at the central warehouse based on requests from service units, regular delivery of drugs from the central warehouse according to a predetermined schedule, or working with the nearest pharmacy to order drugs according to the needs of patients at the Puskesmas. Drug write-off at the Puskesmas is carried out for medicines that have passed their expiration date. All puskesmas have the habit of recording and reporting drugs, but the frequency of recording and reporting can vary